2000
DOI: 10.1046/j.1365-2443.2000.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

ORC1 interacts with c‐Myc to inhibit E‐box‐dependent transcription by abrogating c‐Myc–SNF5/INI1 interaction

Abstract: Background: The c-myc oncogene product (c-Myc) is a transcription factor that forms a complex with Max and recognizes the E-box sequence. c-Myc plays key functions in cell proliferation, differentiation and apoptosis. As for its activity towards cell proliferation, it is generally thought that c-Myc transactivates the E-box-containing genes that encode proteins essential to cell-cycle progression. Despite the characterization of candidate genes regulated by c-Myc in culture cells, these have still not been ®rm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…In yeast and human cells, where ORC1 participates in gene silencing (13)(14)(15), changes in the histone modification status occur in the vicinity of the genomic region affected. We have found that Arabidopsis ORC1 also plays a role as a transcriptional regulator; but there are two novel features in its mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In yeast and human cells, where ORC1 participates in gene silencing (13)(14)(15), changes in the histone modification status occur in the vicinity of the genomic region affected. We have found that Arabidopsis ORC1 also plays a role as a transcriptional regulator; but there are two novel features in its mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ORC1 participates in repression of yeast HMR and HML silent mating type loci (13), and human aldolase B (14) and c-Myc genes (15). Mutations of several ORC subunits in multicellular organisms cause pleiotropic phenotypes including chromosomal abnormalities, cell cycle arrest or zygotic lethality (16)(17)(18).…”
mentioning
confidence: 99%
“…This activation is at least in part due to the recruitment of the TRRAP-GCN5 histone acetylase complex (McMahon et al, 2000). Activation apparently also requires the presence of SNF5/INI1 and possibly the entire SWI/SNF complex (Cheng et al, 1999;Takayama et al, 2000). This observation suggests that loss of an intact SNF5/INI1 protein will cause down-regulation of c-MYC activation.…”
Section: What About Snf5/ini1?mentioning
confidence: 99%
“…Since many candidate genes for transactivation have recently been identified by using the microarray method (7,8), identification of the bona fide target genes of c-Myc should be possible. For its versatile functions, c-Myc associates with various factors other than Max (5), including p107 (9, 10), TBP (11,12), Bin-1 (13), AMY-1 (14), TRRAP (15), PAM (16), ␣-tubulin (17), MM-1 (18), and Cdk inhibitor p21 (19), which bind to the N-proximal region of c-Myc, and also YY-1 (20), Miz-1 (21), AP2 (22), Nmi (23), BRCA1 (24), SNF5 (25), CBF-C/NF-YC (26), cdr2 (27), MSSP (28), CDC6 (29), and Orc1 (30), which bind to the Cproximal region. These binding proteins are thought to modulate c-Myc function, and mutation of the proteins or disregulated expression of their genes may lead to cell transformation by c-Myc.…”
mentioning
confidence: 99%